The safe removal of a superior mediastinal foreign body by mediastinoscopy: a case report - Takashi Sakuma; Tatsuro Tamura; Mikio Nambara; Ken Gyobu; Mami Yoshii; Takahiro Toyokawa; Shigeru Lee; Hiroaki Tanaka; Kazuya Muguruma; Masakazu Yashiro; Masaichi Ohira; Kiyoshi Maeda (Surgical Case Reports)
Abstract Background Mediastinal foreign bodies might cause mediastinal organ injury or mediastinal abscess. The prompt removal surgery of mediastinal foreign bodies is needed to prevent those complications. We report a case in which a mediastinal foreign body was removed by video-mediastinoscopy. Case presentation The patient, a 74-year-old man with a chief complaint of hoarseness, was referred to our department for surgical management of a wooden foreign body that had traumatically migrated into the superior mediastinum. During the surgery, the video-mediastinoscopy was introduced under the pneumomediastinal pressure. We could dissect the scar tissue and remove the azalea tree branch safely and carefully, without damaging the other mediastinal organs. He was discharged on postoperative day 5, with no complications. Conclusions Video-mediastinoscopic approach under pneumomediastinal pressure is minimally invasive and could provide wide surgical view. Therefore, we consider it useful and effective for removal of foreign bodies in the mediastinum.